KONTSTRUKSI BUDAYA MAPALUS DALAM KEHIDUPAN MASYARAKAT MINAHASA - Lumintang, Juliana (Sam Ratulangi University, 2015)
ABSTRACTLong-term goal of this research is to inventory the mapalus culture in public life in order to preservelocal culture in the District of North Langowan Minahasa Regency. Specific target in this study knowntypes mapalus culture in a society that is still going on in the social activities of the community as wellas the perceived benefits of the public against the mapalus activities. The data collected in this studyare primary data and secondary data. The primary data were taken, among others, by (1) Interviewswith respondents who are members of the group mapalus; (2) In-depth interviews to key informantssuch as mapalus group leaders, village elders, community leaders, religious leaders and localgovernment officials; (3) Observations participate for 5 days in each village. While secondary dataobtained from government and non-government agencies with library research methods andliterature.Based on the above results it can be concluded that mapalus or commonly known as' helping thecounty Minahasa terkonstruks strongly and become lifestyle Minahasa community itself.With the passage of time, the development of mapalus the previous form of agricultural labor has beenreplaced mapalus denganjenis other mapalus namely mapalus grief and mapalus marriage. Of thesecond kind is a very strong mapalus is mapalus grief caused grief events can not be predicted when itwould happen so that a sense of responsibility and awareness of the whole society is higher.Keywords: Culture Mapalus